Contour furrowing reduces erosion and enhances soil moisture on semiarid hillslopes - Mondaca, Pedro; Lebuy, Roxana; Rojas, Sergio; Aguas, Javier; Celis-Diez, Juan L.; Díaz-Siefer, Pablo (Geoderma Regional, 2024)
Water scarcity and soil erosion are global problems with socioeconomic consequences for small-scale farmers, especially in semiarid areas. Small-scale farmers scarcely consider techniques for reversing this situation due to uncertain outcomes and high costs. In this study, we hypothesized that contour furrowing, a simple and accessible technique, would effectively increase soil moisture and mitigate soil erosion. In addition, we hypothesized that vegetation is also a contributing factor. We performed a field experiment to evaluate the effect of four treatments on soil moisture (until 1 m depth) and soil loss: bare and unmanaged soils (CON); bare soils managed with contour furrowing (CF); soils with shrub cover (VEG); and CF + VEG. Each treatment was monitored on six hillslopes of agricultural communities in a semiarid area of central Chile for one year. We found that the minimal soil water content recorded in the soil profiles of the CF, VEG, and CF + VEG plots was significantly greater than in the CON plots (with increases of 16%, 22%, and 13%, respectively, compared to CON). The CF and VEG treatments conserved soil moisture during the dry season and demonstrated more effective soil–water recharge after the first rain. However, the combined CF + VEG treatment retained less water in the soil profile than the single treatments. On the other hand, all treated plots showed lower soil loss than the CON treatment (mean of 0.68 t ha−1 year−1). We concluded that contour furrowing effectively enhances soil and soil-water conservation on bare hillslopes. Moreover, it is a low-cost technique that engaged those farmers looking to enhance sustainability and productivity on their lands. [Display omitted] •Keylines, with a geomorphological approach, increased water availability and mitigated runoff.•The geomorphological technique in sites with vegetation can decrease soil moisture but mitigate soil erosion.•The geomorphological technique with vegetation can conserve soil moisture during the dry season.•Techniques were validated in the field and taught to farmers.